PEMBENTUKAN KEPRIBADIAN AKHLAK ISLAMI SISWA SEKOLAH DASAR - Miswar, Miswar (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The formation of the character of the child actually starts early, from home and then continued by educational institutions (schools). This study aims to analyze the formation of islamic personalities of elementary school students. Using the study approach, the results show that there are many ways that can be done in shaping the personality of learners. Because parents do not have enough time and a more comprehensive educational capacity, teachers are an extension of the hands of parents in shaping their child's personality. Efforts that can be made by teachers are through: 1) indoctrination approach, 2) moral reasoning approach, 3) forecasting concequence approach, 4) value classification approach, and 4) ibrah and amtsal approach.